2008
DOI: 10.1111/j.1460-9568.2008.06515.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of music imagery and the effect of musical expertise

Abstract: Although the influence of long-term musical training on the processing of heard music has been the subject of many studies, the neural basis of music imagery and the effect of musical expertise remain insufficiently understood. By means of magnetoencephalography (MEG) we compared musicians and nonmusicians in a musical imagery task with familiar melodies. Subjects listened to the beginnings of the melodies, continued them in their imagination and then heard a tone which was either a correct or an incorrect fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 70 publications
(167 reference statements)
5
81
1
4
Order By: Relevance
“…Studies of perceptuomotor integration in music, however, have mainly studied classically-trained musicians, frequently contrasted with non-musicians (Ohnishi et al, 2001;Baumann et al, 2007;Haslinger et al, 2005;Drost et al, 2005;Bangert et al, 2006;Mutschler et al, 2007;Herholz et al, 2008;Trimarchi and Luzzatti, 2011;Novembre and Keller, 2011;Stewart et al, 2013). This comparison restricts the scope of the study of the neural substrate of musical skill considerably.…”
Section: Introductionmentioning
confidence: 95%
“…Studies of perceptuomotor integration in music, however, have mainly studied classically-trained musicians, frequently contrasted with non-musicians (Ohnishi et al, 2001;Baumann et al, 2007;Haslinger et al, 2005;Drost et al, 2005;Bangert et al, 2006;Mutschler et al, 2007;Herholz et al, 2008;Trimarchi and Luzzatti, 2011;Novembre and Keller, 2011;Stewart et al, 2013). This comparison restricts the scope of the study of the neural substrate of musical skill considerably.…”
Section: Introductionmentioning
confidence: 95%
“…Cognitive psychology has shown that imaginal experiences are psychologically real in so far as they can be quantified, and because they share features of real perception, including temporal accuracy and pitch acuity (57,58). Several neuroimaging studies have shown the neural reality of this phenomenon because, even in the absence of sound, portions of belt or parabelt auditory cortex are consistently recruited when people perform specific imagery tasks (59,60). This imagery ability is relevant here because it shows that auditory cortex must contain memory traces of past perceptual events, and that these traces are not merely semantic in nature, but rather reflect perceptual attributes of the originally experienced sound.…”
Section: Neurobiology Of Musical Cognitionmentioning
confidence: 99%
“…These studies have used tasks such as judging the relative height of the pitches of two lyrics in an imagined song (Zatorre, Halpern, Perry, Meyer, & Evans, 1996), imagining the continuation of a familiar melody given its opening notes (Halpern & Zatorre, 1999) or during gaps in an ongoing melody (Kraemer, Macrae, Green, & Kelley, 2005), and comparing the similarity of the timbres of two imagined instruments (Halpern, Zatorre, Bouffard, & Johnson, 2004). Auditory cortical involvement is also indicated by MEG data showing an early preattentive response to unexpected incorrect continuations of imagined melodies (Herholz, Lappe, Knief, & Pantev, 2008). Finally, the role of auditory cortex was supported by lesion data showing deficits in musical imagery following excision of right temporal cortex (Zatorre & Halpern, 1993).…”
Section: Introductionmentioning
confidence: 97%